The masonic question and the Italian left: From the ‘excommunication’ of the socialist congress of 1914 to the first congresses of the Communist International - Novarino, Marco (2020)
The anti-masonic motion, voted in the congress of the Partido Socialista Italiano (PSI) in 1914, it settled a polemic that had begun in the first years of the 20th Century, and that had split the relationship between both organizations. When, in 1919, the PSI decided to adhere to the new Communist International, the masonic polemics was part of the debates that took place in the congresses prior to Lenin’s death. Overall, when it was clear that many Italian socialist-freemasons had adhered to the French communist party, the International, mainly due to Trotsky who adopted strict stances on the matter.